Pre-Extension Demonstration and Evaluation of Maize (Zea Mays l.) -Haricot Bean (Phaseolus Vulgaris L.) Intercropping Practices in Midlands of Guji Zone, Southern Oromia, Ethiopia - Girma Amare; Basha Kebede; Dembi Korji (International Journal of Scientific Multidisciplinary Research, 2025)
The Planting two or more crops at the same time and location is known as intercropping. During the 2019 primary rainy season, the work was done in the Guji Zone in Oromia, Ethiopia, as well as the districts of Adola Rede and Odo Shakiso. Calculating the yield output and cost-benefit ratio of haricot bean and maize intercropping techniques under farmer conditions, as well as the preferences of farmers and other stakeholders, are among the objectives of the demonstration. A district's two Kebeles, or sites, were chosen depending on their potential to produce maize and haricot beans. Fifteen farmers were picked from each Kebele/site and placed in a single FRG. As a result, four FRGs with 60 farmers (15 women and 45 men) were formed. Better haricot bean (Haramaya) and maize (BH-546) cultivars have been shown by growing the crops alone in 100 m2 plots of each species, with the necessary amounts of seed and fertilizer placed 40 cm apart from one another and 10 and 75 cm apart for the haricot bean and maize, respectively. Field days, technological reviews, exchange visits, and training enhanced farmer-to-farmer knowledge of haricot bean-corn intercropping methods. Intercropping metrics, measurement, in-person interviews, and observation were employed to obtain the information. Descriptive statistics and a qualitative examination of the farmers' preferences were used to analyze the data. According to the demonstration results, a net return of 28,007.67 ETB/ha was achieved by producing 2.746 tons of maize and 2.323 tons of haricot beans per hectare